Expression of discrimination against children with disabilities in the Lithuanian health care system - Baranauskienė, Ingrida (Special Education, 2021)
In the present article, I aim to answer the questions: what is the situation of children with disabilities and their parents in the healthcare system in Lithuania? Are they discriminated against? If discrimination against children with disabilities persists, what is its manifestation? Is it possible to see a link between discrimination against children with disabilities and attitudes towards parents of children with disabilities? These and other similar questions reflect the scientific problem of the article. The research questions are concretized by the research object – expression of discrimination of children with disabilities and their parents in the Lithuanian health care and related systems. The findings of the research prove that there are cases when children with disabilities experience discrimination in the Lithuanian health care system. The expression of discrimination against children with disabilities and their parents is related to: open disregard of the child and his/her mother, which escalates into an underestimation of the child as a person; neglect of infants from children’s home in the hospital; unequal treatment conditions for children with different disabilities; discrimination against children with intellectual disabilities in access to dental treatment; irresponsible administering or not administering medicines to children with disabilities; together with children, their mothers are also discriminated against; low-quality services that violate the dignity of the child and the family. Not only children with disabilities but also their parents can face discrimination in the health care system.